NutritionCalc plus[Cakerapadat] (McGraw-Hill, 2009)
NutritionCalc Plus 3.2 is a suite of powerful self-assessment tools that allow you to monitor your personal diet and health goals. An imporved interface and the realibility of the ESHA database make NutritionCalc Plus 3.2 your best choice for diet analysis software